Animal farm : a fairy story - Orwell, George, 1903-1950. (2003)
Orwell's 1945 fable about the power struggles among animals on a farm parallels the situation in Russia at the time as Orwell saw it; the characters include the ruthless pig Stalin, his idealistic Trotsky-like adversary, and the simple, kindly horse who represents the common man. All animals are equals but some animals are more equal than others. George Orwell's classic satire of the Russian Revolution is the account of the bold struggle, initiated by the animals, that transforms Mr. Jones's Manor Farm into Animal Farm, a wholly democratic society built on the credo that all animals are created equal. Out of their cleverness, the pigs Napoleon, Squealer, and Snowball emerge as leaders of the new community in a subtle evolution that proves disastrous. The climax is the brutal betrayal of the faithful horse Boxer, when totalitarian rule is re-established with the bloodstained postscript to the founding slogan: but some animals are more equal than others. War is peace. Freedom is slavery. Ignorance is strength.
14+
Keywords: Domestic animals -- Fiction; Totalitarianism -- Fiction; Political fiction; Satire